(untitled) (ALPHA. Journal of Arts, Literature and Philosophy, 2003)
In Spanish literary historiography, nineteenth-century fantastic literature has traditionally been treated as a minor genre in relation to canonical realist literature, considering it a romantic remnant with escapist tendencies. However, in the last decades of the 20th century, attention began to be paid especially to the famous work of recognized writers such as Gustavo Adolfo bécquer, Benito Pérez Galdós or Rosalía de Castro. In the 1990s, for example, a special issue of the magazine Anthropos (154/155) and two editions by Jaune Pont, from the University of Lleida, were published in Spain, dedicated especially to Hispanic fantasy literature.